2012
DOI: 10.1097/jac.0b013e31823b0fbe
|View full text |Cite
|
Sign up to set email alerts
|

Care Guides

Abstract: Lay persons ("care guides") without previous clinical experience were hired by a primary care clinic, trained for 2 weeks, and assigned to help 332 patients and their providers manage their diabetes, hypertension, and congestive heart failure. One year later, failure by these patients to meet nationally recommended guidelines was reduced by 28%, P < .001. Improvement was seen in tobacco usage, blood pressure control, pneumonia vaccination, low-density lipoprotein cholesterol levels, annual eye examinations, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Similar studies have approached this challenge by creating dichotomous variables -such as improved control (yes/no) or achievement of guideline-based control (yes/no)—that can summarize each patient’s disease-specific outcome [17]. This approach is intuitive but loses a significant amount of information and fails to capture incremental improvements.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Similar studies have approached this challenge by creating dichotomous variables -such as improved control (yes/no) or achievement of guideline-based control (yes/no)—that can summarize each patient’s disease-specific outcome [17]. This approach is intuitive but loses a significant amount of information and fails to capture incremental improvements.…”
Section: Design and Methodsmentioning
confidence: 99%
“…[36][37][38][39][40] Of the eight pre-post studies, five showed a significant decrease in ED visits relative to a baseline measurement, [41][42][43][44][45] and one had no significant decrease. 46 Two pre-post studies did not indicate statistical significance; of these, one intervention resulted in a decrease in ED visits 47 and one in an increase in ED visits. 48 There were three cohort studies that examined ED use, two of which showed significant decreases in ED use in the intervention group.…”
Section: Emergency Department Visitsmentioning
confidence: 99%
“…34,35,37,39,40,51 One showed a significant decrease relative to the control. 36 Of the seven pre-post studies that assessed hospitalization, all showed a decrease in hospitalizations, 41,[43][44][45][46][47][48] but only five indicated statistical significance. 41,[43][44][45][46] Three cohort studies assessed the effect of the intervention on hospitalizations.…”
Section: Emergency Department Visitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies demonstrate the value of incorporating CHWs into interdisciplinary health teams. 4–7 For example, the Community Outreach and Cardiovascular Health Program (COACH) was a 12-month nurse practitioner (NP)-CHW comprehensive intervention for patients with cardiovascular disease in Baltimore. In this randomized controlled trial (RCT), participants in the intervention arm received tailored lifestyle and diet coaching, home-based exercise programs, home visits, and telephone reminders of appointments, compared with participants in the control arm who received enhanced usual care consisting of care from their providers, including feedback on their cardiovascular risk also given by the provider.…”
Section: Introductionmentioning
confidence: 99%